2013
DOI: 10.1016/j.pain.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Course and prognosis of older back pain patients in general practice: A prospective cohort study

Abstract: The aim of the current study was to determine the course of back pain in older patients and identify prognostic factors for non-recovery at 3 months' follow-up. We conducted a prospective cohort study (the BACE study) of patients aged >55 years visiting a general practitioner (GP) with a new episode of back pain in the Netherlands. The course of back pain was described in terms of self-perceived recovery, pain severity, disability, pain medication, and GP visits at 6 weeks' and 3 months' follow-up. Prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 23 publications
3
43
1
Order By: Relevance
“…In addition, while lumbar patho-anatomical changes increase with age, pathology has not been strongly associated with pain severity or found to predict pain recovery. 2,24,25,51 However, use of imaging in future studies will elucidate whether interactions exist between pathology and TENS response among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while lumbar patho-anatomical changes increase with age, pathology has not been strongly associated with pain severity or found to predict pain recovery. 2,24,25,51 However, use of imaging in future studies will elucidate whether interactions exist between pathology and TENS response among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Adults with acute back pain typically have a good prognosis [3,4], but after 3 months of symptoms, the prognosis is considerably less favorable as the improvement in pain and disability is small for the patients with ongoing pain and disability [3,5,6]. Little is known about the prognosis for new episodes of back pain for older adults, but initial evidence suggests it is less favorable [7]. A greater proportion of older adults continue to have back pain and limited function at 3 months compared with the studies of younger adults [3,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the prognosis for new episodes of back pain for older adults, but initial evidence suggests it is less favorable [7]. A greater proportion of older adults continue to have back pain and limited function at 3 months compared with the studies of younger adults [3,4,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is not part of the prognostic scale, yet studies have found that duration of symptoms is, not surprisingly, a predictor of future duration of spine symptoms. 11,12 Clinicians choosing to use this scale should consider taking duration into account, especially if the back pain is functionally impairing.…”
mentioning
confidence: 99%